Differentiation potential of the fetal rat liver-derived cells. - Zygmunt Pojda; Jerzy Moraczewski; Tomasz Oldak; Marzena Jastrzewska; Agnieszka Gajkowska; Iwona Grabowska; Eugeniusz K Machaj (Folia Histochemica et Cytobiologica, 2005)
Mesenchymal stem cells derived from bone marrow or several fetal tissues can be expanded and differentiated into other cell lines. The fetal liver is the source of early hematopoietic cells and also, as a fetal tissue, may be considered as a source of pluripotent stem cells. The differentiation potential of fetal rat liver cells have been examined. Freshly isolated liver cells from 14-d fetuses were cultured in Dulbecco medium supplemented with 10% FCS. The plastic-adherent cells were then passaged up to 10 times. Freshly isolated cells and cells from every passage were cultured in hematopoiesis-promoting environment that consists of methylcelulose supplemented with FCS, rat IL-3, human IL-6 and Epo. Parallely these cells were incubated in co-culture with rat muscle satellite cells (Dulbecco medium with 10% FCS and 10% HS) to examine their myogenic potential. Culture in methylcelulose resulted in a high number of GM and Mix colonies in case of freshly isolated liver cells and the number of colonies decreased according to the number of passages. In case of cells from 4th passage, there ware no hematopoietic colonies in culture. In contrast--freshly isolated cells were not able to fuse with rat satellite cells and form the myotubes. This ability appeared in plastic-adherent cells just from the second passage and increases to 5th passage. The cells from every next passage up to 10th when co-cultured with satellite cells participated in myotube formation at the same high level. This result may suggest that in the 14-d rat liver there exist at least two subpopulations of cells: the non-adherent hematopoietic cell population, and the population of plastic-adherent cells capable of differentiating into myotubes. Since the attempts to redifferentiate hematopoietic subpopulation into myopoiesis, or myopoietic subpopulation into hematopoiesis failed, it may be concluded that at least under our experimental conditions the fetal liver cells do not reveal the "plasticity" features.